Assessment of the relationship between gastroesophageal reflux disease, smoking and dental wear: narrative review of the literature (Research, Society and Development, 2022)
The objective of this study was to evaluate the relationship between gastroesophageal reflux disease (GERD), smoking and tooth wear. A narrative review was conducted, performing an electronic literature search using the PubMed/Medline platform. Cross-sectional, cohort and case- control studies carried out in adults were included, addressing at least two of the three research topics. Animal studies, case reports, literature reviews, book chapters, letters, commentaries, editorials, and in vitro studies were excluded. There were no restrictions regarding language and publication date. The search resulted in 523 articles, 46 of them met the inclusion criteria. A total of 156,843 people from 20 countries participated in the selected studies. Most articles found a significant association between smoking and the occurrence of GERD, which can be explained by mechanisms involving Lower Esophageal Sphincter (LES) relaxation, reduced salivary secretion and increase in gastric emptying time. In addition, individuals with GERD may have reduced pH in the oral cavity, which can lead to degradation of dental structures, a process that can be exacerbated by the direct impact of smoking. The results of this study suggest that there is a positive relationship between GERD, smoking and tooth wear. However, further prospective studies evaluating the interaction of these three factors are needed to corroborate these findings.